2013
DOI: 10.1097/mlr.0b013e3182a95d86
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Diagnosis and Treatment of Nonmalignant Pain in the United States, 2000–2010

Abstract: Background Escalating rates of prescription opioid use and abuse have occurred in the context of efforts to improve the treatment of non-malignant pain. Objectives To characterize the diagnosis and management of non-malignant pain in ambulatory, office-based settings in the United States between 2000 and 2010. Design, setting, and participants Serial cross-sectional and multivariate regression analyses of the National Ambulatory Medical Care Survey (NAMCS), a nationally representative audit of office-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
166
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(167 citation statements)
references
References 18 publications
1
166
0
Order By: Relevance
“…[1][2][3][4][5][6] Increased use is variously quantified as number of opioid prescriptions, 7 percentage of primary care visits resulting in opioid prescription, [8][9][10] opioid sales in milligrams per 10,000 capita, 11 and average dose of medication per health plan participant. 12 However, these data can be difficult to interpret.…”
Section: Background/introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Increased use is variously quantified as number of opioid prescriptions, 7 percentage of primary care visits resulting in opioid prescription, [8][9][10] opioid sales in milligrams per 10,000 capita, 11 and average dose of medication per health plan participant. 12 However, these data can be difficult to interpret.…”
Section: Background/introductionmentioning
confidence: 99%
“…1,2 Eighty percent of opioid prescriptions worldwide are distributed in the United States. 3 From 1999 to 2010, opioid sales in the United States quadrupled, and in 2012, an estimated 259 million prescriptions for opioid medications were written.…”
mentioning
confidence: 99%
“…1 Since 1999, the rate of overdose deaths attributable to prescription opioids and the number of opioid prescriptions have quadrupled. 1,2 Understanding the impact of this epidemic on adolescents is necessary to guide prevention efforts for this population. In the 2015 National Survey on Drug Use and Health, a household survey, it is estimated that nearly 6% of 12-to 17-year-olds misused prescription psychotherapeutic drugs in the past year, whereas in the school-based Monitoring the Future survey, it is reported that a higher annual prevalence of 12.0% among 12th-graders misused prescription psychotherapeutic drugs during the same time period.…”
mentioning
confidence: 99%